A Study On The Motivational Factors On Buying Behaviour Of Eco-Friendly Products In Thoothukudi City (International Journal of Food and Nutritional Sciences, 2022)
The main aim of the eco-friendly product is to guarantee the safety of human beings, flora and fauna in terms of mortality, age, diseases, and illnesses by minimizing the use of all hazardous chemicals and other variables which pollute the environment. To attain this goal the producers tend to reduce the environmental pollutants, using energy conservative resources, sustainable use of natural resources, using recyclable resources, using the simplified waste treatment and disposal in the products, emphasize safety-consciousness, and include environmental safety information on product labels. The main objective of the study is to explore the socio-economic profile of the respondents and to study the factors that motivate the consumers of eco-friendly products. The consumers of eco-friendly users in Thoothukudi Corporation are the universe of this study. The researcher adopts area sampling to select the sample for the study. The researcher randomly selects 5 wards from the Thoothukudi Corporation and finds eco-friendly consumers by asking every person in the area. The majority (46.58 percentage) of the respondents who consume eco-friendly products have a family income below Rs. 2,00,000 per annum. The majority (53.30 percentage) of the male respondents who consume eco-friendly products are unmarried and the majority (59.60 percentage) of the female respondents are married. The null hypotheses are not rejected at a 5% significance level. Hence, there is no significant mean difference between male and female respondents in respect to the factors impact of the product, the reputation of the product, and appearance of the product.